Hubungan Intensitas Kebisingan dan Tekanan Darah Tenaga Kerja di Sentra Industri Tembaga Desa Tumang Cepogo, Boyolali - Arum Prasetyaningsih; Agus Suwarni; Indah Werdiningsih (Poltekkes Kemenkes Yogyakarta, 2014)
One of the negative impacts resulting from the activities of the copper industries in Tumang Villa-ge of Cepogo, Boyolali, is noise. One of physiological disorders caused by the presence of excessive noise is the increase of blood pressure. Based on the preliminary study, it was identi-fied that the noise had exceeded the threshold value. This study was aimed to determine the relationship of noise exposure with blood pressure among labor of the copper industries by conducting a descriptive study which followed cross sectional approach. From 26 industries with criteria of at least employ 5 workers, seven industries and a total of 35 respondents were se-lected by using stratified random sampling method. The data were obtained through interview, noise intensity mesurement using sound level meter, and blood pressure measurement using spygnomanometer. The collected data were then processed descriptively and analytically by applying Spearman Rank test at ?=0,05. The results showed that the average of noise inten-sity was observed as 81.02 dB, with the minimum and maximum values were recorded at 71.01 dB and 86.82 dB. Meanwhile, the blood pressure measurements showed that the majority of workers has stable systolic blood pressure (48,57 %) and diastolic blood pressure (65,71 %). The statistical test concluded that noise intensity has no association with systolic blood pressure, but has significant relationship with the diastolic one.